ENHANCEMENT OF GENERALISED SELECTIVE COMBINER USING COMBINED MODULATION SCHEMES OVER RAYLEIGH FADING CHANNEL - HAMMED LASISI; FUNMILOLA ADEAGBO; BOLATITO ADERINKOLA (Journal of Engineering Studies and Research)
This research paper focused on the enhancement improvement of communication system using a combined modulation signal of Quadrature Amplitude Multiplexing and Orthogonal-frequency division multiplexing (OFDM) using a performance metrics of bit error rate (BER) and Signal to Noise Ratio (SNR) tested on a Rayleigh fading channel. The GSC is introduced at the receiving end to give a better received signal with in turn will result in better Quality of Service. The bit error rate (BER) performance of this type of systems are evaluated in the Rayleigh fading channel using Additive White Gaussian Noise (AWGN) channel as an ideal model.